Disturbance Modeling on Transmission Lines Using Wavelet Transform Method: A Review - Sitti Amalia; Mardini Hasanah; Yusreni Warmi; Novizon Novizon; Abdul Rajab (Andalas Journal of Electrical and Electronic Engineering Technology, 2022)
This paper introduces a number of methods for identifying disturbances on transmission lines and provides algorithms for classifying various disturbance types. working with the discrete wavelets transform (DWT) and various embedded systems techniques using a simulator to carry out digital simulations of system trials using the controlled technique, the nature of disturbance in distinct sub-systems is determined. The analysis of transmission lines using the wavelet transform is the main topic of this study, along with techniques for transmission line protection. These factors include channel capacity, channel length, simulation software, mother wavelet type, parameters, sampling frequency, and type of disturbance analysis.